KEEFEKTIFAN KALIMAT DALAM TEKS BERITA SISWA KELAS VIII SMP NEGERI 16 PADANG - Khairalfi Jumanisa Amril; Emidar Emidar (Universitas Negeri Padang, 2020)
ABSTRACTThe purpose of this study is to describe the effectiveness of sentences in the student news text in terms of five things. First, the effectiveness of sentences in terms of clarity of structure, there are 82 (16.56%) errors. The ineffectiveness of the sentence is in the active/ passive structure (14 errors), the subject is not an explanation (33 errors), the predicate is not lost (15 errors), the description is not in the form of the subject (10 errors), and the subject is not lost (10 errors). Second, the effectiveness of the sentence in terms of the logical meaning there are 58 (11.72%) errors. The ineffectiveness of the sentence lies in the logical relationship S and P (49 errors) and the logical relationship of details or parallel meaning (9 errors). Third, the effectiveness of sentences in terms of word savings there were 40 (8.08%) errors. The ineffectiveness of the sentence is on one subject from the same subject (27 errors) and one word from several synonymous words (13 errors). Fourth, the effectiveness of sentences in terms of word stiffness there are 34 (6.87%) errors. Fifth, the effectiveness of sentences in terms of spelling accuracy is 281 (56.77%). Ineffectiveness of the sentence lies in the use of capital letters (102 errors), prepositions (33 errors), punctuation (85 errors), and writing words (61 errors). Based on these results it can be concluded that the sentences in the explanatory text of eighth grade students of SMP Negeri 16 Padang are not effective. This is evidenced from the 210 sentences studied, there were 22 (10.48%) effective sentences and 188 (89.52%) ineffective sentences with 495 errorsKata Kunci: Keefektifan Kalimat, Teks Berita